A Prospective Psychological Study of Patients with Undiagnosed Episodes of Disturbed Consciousness - L. D. Blumhardt; D. Barnes; S. J. Howell; E. Ghadiali (Behavioural Neurology)
We have carried out a prospective psychological and clinical study of neurological out-patients with episodes of disturbed consciousness that were mostly unexplained after clinical assessments and prolonged follow up. When compared with matched healthy subjects, both the undiagnosed patients and a control group with chronic epilepsy, had evidence of abnormal personality and psychological disturbance. However, in the undiagnosed patients there were significant differences between two subgroups defined by the results of clinical follow up. Patients whose symptoms resolved spontaneously were psychologically indistinguishable from healthy control subjects, whereas patients whose unexplained symptoms continued, with or without empirical treatment trials, had highly abnormal personality profiles. Although the basic psychological tests we used cannot reliably separate individual patients with epilepsy from those with non-epilepsy, they do have some predictive value with respect to the prognosis of unexplained symptoms. Further detailed prospective studies may help to establish the relationship between psychological disorder and unexplained symptoms and perhaps reduce the need for repeated, expensive investigations.